PERANAN ENERGI KAYU BAKAR DAN MASALAH PERENCANAANNYA (The role of fuelwood energy and its planning problems) - Hatiyatno Dwiprabowo (Jurnal Penelitian Hasil Hutan, 1993)
The role of fuelwood energy in filling energy demand in Indonesia has bean substantial and it still will be important in the future. For instance, in 1989 it is estimated that the contribution of furlwood energy to total energy consumption in the country was around 45%. The general policy an national energy encourages development of renewable resources and new sources of energy to fill energy needs. Fuelwood as one of renewable resources will play important role as the development costs for other renewable resources remain high.The efforts to fill the fuelwood demand need careful planning and strategy formulation. However, presently data produced from previous surveys and studies are iadequate to support a database for planning purposes.This paper is almed to review the role of fuelwood energy and its planning challenges with respect to data availability, methodology, and institution.